Adolescents' advertising literacy and privacy protection strategies in the context of targeted advertising on social networking sites: implications for regulation. Issue 3 (17th August 2020) - Zarouali, Brahim; Verdoodt, Valerie; Walrave, Michel; Poels, Karolien; Ponnet, Koen; Lievens, Eva
Abstract : Purpose: This study aims to investigate the development of adolescents' advertising literacy and privacy protection strategies in the context of targeted advertisements on social networking sites (SNSs). Design/methodology/approach: A survey was conducted among 374 adolescents between 12 and 17 years of age, and 469 young adults (18–25 years) served as a comparative benchmark. Findings: Results indicate that advertising literacy increases progressively throughout adolescence, and reaches adult-like levels only by the age of 16. In addition, adolescents have an inadequate awareness of commercial data collection practices. This awareness slowly increases as a function of their age until it reaches an adult level around the age of 20. Finally, findings reveal that adolescents take little action to cope with targeted advertisements by means of privacy protection strategies. Practical implications: This paper devotes much attention to the formulation of specific recommendations for EU policymakers and regulatory bodies. In addition, it also holds implications for advertisers (e.g. the need for more in-depth data protection impact assessments), social media providers (e.g. adolescent-friendly privacy policy) and social caretakers (e.g. achieving advertising literacy and privacy education). Originality/value: This paper fulfills the need to investigate adolescents' advertising literacy and privacy-protective behaviors on SNSs, and, in turn, directly translates these insights into recommendations that can underpin the rationale of regulatory or policy decisions on a European level.